The process of forming knowledge: In the study of ontology, epistemology, and axiology - Rosida, Rina Fatiya; Amaliah, Laily Nur; Mahardika, I Ketut; Suratno, Suratno (International Journal for Educational and Vocational Studies, 2023)
Humans acquire knowledge based on their abilities as beings who think, feel, and sense. Knowledge is the result of knowing, and this occurs after people sense a certain object. Sensing occurs through the five human senses, namely the senses of sight, hearing, smell, taste, and touch. Most of human knowledge is obtained through the eyes and ears. The purpose of this study is to describe science from a philosophical view from the perspective of ontology, epistemology, and axiology. Ontology, epistemology, and axiology are the basis for the development of science. Ontology can be defined as the essence of an existence which includes everything that exists. Knowledge comes from one's appreciation and understanding of the situation. Humans as subjects try to express, recognize, and know the objects around them. The object is in the form of reality or facts that function as a stimulus to the awareness possessed by humans. Knowledge is obtained through a cognitive process, where a person must first understand or recognize science to know that knowledge. There are three foundations in knowledge, namely the ontological, epistemological, and axiological foundations.